The anthelmintic flubendazole blocks human melanoma growth and metastasis and suppresses programmed cell death protein-1 and myeloid-derived suppressor cell accumulation. (10th September 2019) - Li, Yue; Acharya, Grishma; Elahy, Mina; Xin, Hong; Khachigian, Levon M.
Abstract: The incidence of melanoma is increasing faster than any other cancer. In recent years, treatment of melanoma and a range of other deadly cancers has involved immunotherapy with programmed cell death protein-1 (PD-1)/PD-1 ligand (PD-L1) checkpoint blockade which has improved survival. However, many patients do not respond or have partial response, survival benefit is in the order of months and all available PD-1/PD-L1 strategies are antibodies requiring intravenous infusion. There are no clinically approved small molecule pharmacologic inhibitors of the PD-1/PD-L1 system. The benzimidazole derivative flubendazole is a widely used anthelmintic available over the counter in Europe. Here we demonstrate the ability of flubendazole to inhibit human melanoma growth and spread in mice. Flubendazole's ability to block tumor growth and spread was comparable to paclitaxel. Anti-tumor effects were observed when flubendazole was delivered systemically not locally. Flubendazole inhibited CD31/PECAM-1 staining indicating suppression of tumor angiogenesis. Most surprisingly, flubendazole inhibited PD-1 levels within the tumors, but not PD-L1. Western blotting and flow cytometry revealed that flubendazole inhibits PD-1 expression in cultured melanoma cells. Flubendazole also reduced myeloid-derived suppressor cell (MDSC) levels in tumor tissue. Further we found that flubendazole inhibited active (phospho-Tyr 705 ) signal transducer and activator of transcription (STAT3), an upstream regulator of PD-1 expression. These findings uncover that flubendazole is a novel small molecule inhibitor of not only melanoma growth and spread but also of PD-1 and MDSC. Highlights: There are no clinically available PD-1/PD-L1 inhibitors for cancer. We found that flubendazole, an antihelmintic available without a prescription in Europe, is a novel small molecule pharmacologic inhibitor of PD-1. Flubendazole abrogates growth and metastasis of human melanoma grown as xenografts in mice. Flubendazole suppresses angiogenesis in human melanoma. Besides inhibiting PD-1, flubendazole inhibits phospho-(Tyr 705 ) STAT3 in human melanoma cells and within treated tumors. Flubendazole also suppresses myeloid-derived suppressor cell (MDSC) accumulation within tumors.